Intelligence Activity of the Law Enforcment Services in Function of More Efficient Fight Against Organised Crime - Masleša, Ramo (Kriminalističke teme, 2004)
In this paper author elaborates issues related to the new concept and models of intelligence activities by Law Enforcement agencies, combating Organised Crime. Under these topics, special attention will be focus on abuse of human rights in these activities; ethical standards of law enforcement professionals and international standards related the applying of special investigation methods.